The quality of live of patients’ allegic rhinitis after posterior nasal neurectomy at Dr Sardjito General Hospital Yogyakarta, Indonesia 2016 - Wahyu Dwi Kusdaryanto; Windarti Isminarsih; Luh Putu Lusy Indrawati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Allergic rhinitis (AR) is disease by incidence and prevalence of high and is expected to rise to load against the economy and lowering the quality of life of patients.with AR involved many factors and an impact of highly significant on the quality of life and affect the economy. The quality of life patients done to assess the effects and result of surgery.Sino nasal outcome test-20 ( snot-20 ) was one of the instruments specific measurement the quality of life of patients AR. 10 patients who surgery action , obtained improving the quality of life based on snot- 20 observed 28 days after done the act of surgery. Rate the SNOT-20 before surgically obtained 37,3 with DS ± 7,87 and 28 days after done surgically obtained rata-rata snot-20 is 6 with DS ± 2,49. The SNOT-20 pre and post action there are different of significant (p = 0,024 ) .